IMPLEMENTATION OF PSAK 102 IN MURABAHAH FINANCING AT BANK SYARIAH INDONESIA KCP BATANG - Tasya Bria istiqomah; Hari Purwanto; Imam Prayogo (RADJA PUBLIKA, 2025)
This study examines the implementation of PSAK 102 in murabahah financing at Bank Syariah Indonesia KCP Batang. The research employs a descriptive qualitative method, utilizing primary data from interviews and secondary data from financial reports. Findings indicate that BSI KCP Batang has properly applied PSAK 102 in revenue recognition upon transfer of goods ownership. However, discrepancies were identified regarding physical possession of goods and transparency of profit margins. Murabahah financing grew by 20.69% during 2023-2024, demonstrating positive public interest despite remaining below national averages. The study recommends enhanced compliance with sharia accounting standards and improved product socialization to strengthen transparency and accountability.